Promoter‐like sequences regulating transcriptional activity in neurexin and neuroligin genes. (21st August 2013) - Runkel, Fabian; Rohlmann, Astrid; Reissner, Carsten; Brand, Stefan‐Martin; Missler, Markus
Abstract: Synapse function requires the cell‐adhesion molecules neurexins (Nrxn) and neuroligins (Nlgn). Although these molecules are essential for neurotransmission and prefer distinct isoform combinations for interaction, little is known about their transcriptional regulation. Here, we started to explore this important aspect because expression of Nrxn1‐3 and Nlgn1‐3 genes is altered in mice lacking the transcriptional regulator methyl‐CpG‐binding protein2 (MeCP2). Since MeCP2 can bind to methylated CpG‐dinucleotides and Nrxn / Nlgn contain CpG‐islands, we tested genomic sequences for transcriptional activity in reporter gene assays. We found that their influence on transcription are differentially activating or inhibiting. As we observed an activity difference between heterologous and neuronal cell lines for distinct Nrxn1 and Nlgn2 sequences, we dissected their putative promoter regions. In both genes, we identify regions in exon1 that can induce transcription, in addition to the alternative transcriptional start points in exon2. While the 5′‐regions of Nrxn1 and Nlgn2 contain two CpG‐rich elements that show distinct methylation frequency and binding to MeCP2, other regions may act independently of this transcriptional regulator. These data provide first insights into regulatory sequences of Nrxn and Nlgn genes that may represent an important aspect of their function at synapses in health and disease. Neurexins and neuroligins constitute large families of synaptic cell‐surface molecules that play essential roles in neurotransmission and are linked to autism spectrum disorders and schizophrenia. To better understand their gene regulation, we analyze putative promoter regions for transcriptional activity. Expression involves the brain‐specific regulator MeCP2 and methylation frequency, suggesting an unexpected pathway for regulating their distribution, splicing or activity‐dependent plasticity. Abstract : Neurexins and neuroligins constitute large families of synaptic cell‐surface molecules that play essential roles in neurotransmission and are linked to autism spectrum disorders and schizophrenia. To better understand their gene regulation, we analyze putative promoter regions for transcriptional activity. Expression involves the brain‐specific regulator MeCP2 and methylation frequency, suggesting an unexpected pathway for regulating their distribution, splicing or activity‐dependent plasticity.